Maladministrasi dalam Pelayanan BPJS Kesehatan di Rumah Sakit Pemerintah: Analisis Pelanggaran Asas-Asas Umum Pemerintahan yang Baik Perspektif Hukum Administrasi Negara: Studi di RSUD Dr. Wahidin Sudirohusodo Makassar - Raihan A. Hanasi; Siti Nurhaliza Labasir; Lina Syafitri (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
Maladministration in BPJS Kesehatan services at government hospitals remains a persistent challenge that undermines the principles of good governance in Indonesia. This study examines violations of the General Principles of Good Governance (Asas-Asas Umum Pemerintahan yang Baik/AUPB) in the context of BPJS Kesehatan services at Dr. Wahidin Sudirohusodo Regional General Hospital (RSUD), Makassar, South Sulawesi. This research employs a normative-empirical legal method, combining statutory analysis with field data obtained through interviews and documentation. The findings reveal that maladministrative practices—including procedural delays, discriminatory treatment of BPJS patients, inadequate information disclosure, and arbitrary administrative decisions violate several AUPB principles enshrined in Law No. 30 of 2014 on Government Administration. These violations contravene the principles of legal certainty, impartiality, proportionality, and accountability. The study concludes that institutional reforms, strengthened supervisory mechanisms through the Ombudsman of the Republic of Indonesia, and enhanced legal literacy among healthcare workers are necessary to reduce maladministration. This research contributes to the development of administrative law enforcement in the Indonesian public health sector.